INHBB is a novel prognostic biomarker and correlated with immune infiltrates in gastric cancer - Yu, Weifeng; He, Guihua; Zhang, Wang; Ye, Zhenhao; Zhong, Zishao; Huang, Suiping (Frontiers in Genetics, 2022)
Inhibin subunit beta B (INHBB) is a potential prognostic biomarker for a variety of cancers. However, its role in gastric cancer (GC) remains elusive. The differential expression data of INHBB in tumor and normal tissues were extracted from several databases and genetic alterations of INHBB was assessed by cBioPortal. Kaplan–Meier analysis was used to evaluate the survival rate of patients with GC with INHBB and association with clinical features in GC. Cox regression analysis was used to explore the prognostic value of clinical indicators and INHBB in GC, and a nomogram prognostic model was established. In addition, the prediction validity of the nomogram model was assessed by time-depended receiver operating characteristic (ROC) and calibration curves. Functional enrichment analyses were conducted to functionally annotate INHBB. Notably, we found that the quantitative assessment of immune cell subpopulation infiltration correlated with INHBB expression. INHBB expression is upregulated in GC and is correlated with several clinical features including prognostic indicators and a histological type. Genetic alterations were observed in INHBB, its DNA methylation level was negatively correlated with INHBB expression. High INHBB expression is associated with a poor prognosis and is an independent risk factor for prognosis in GC, along with age and residual tumor. The nomogram model showed a good prediction ability and was validated by time-depended ROC and calibration curves. Functional enrichment analysis indicated that INHBB-associated genes were enriched in tumor microenvironment Gene Ontology (GO) terms and was correlated with tumor-associated pathways. INHBB has a regulatory function in immune cell infiltration, especially macrophage infiltration in GC. Specifically, patients with GC with high INHBB expression and high macrophage infiltration have a worse prognosis. INHBB expression was negatively correlated with the expression of chemokines/chemokine receptors and plays a regulatory role in immunoinhibitor/immunostimulator-involved pathways. INHBB is a potential prognostic biomarker for GC and may drive the abnormal activity of critical cancer-associated pathways, potentially contributing to immune cell infiltration to promote GC development.